1987
DOI: 10.1016/s0006-3495(87)83332-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of tissue potassium in vivo using 39K nuclear magnetic resonance

Abstract: 39K nuclear magnetic resonance (NMR) spectra were readily obtained, in vivo, from rat muscle, kidney, and brain in 5-10 min with signal-to-noise ratios of approximately 20:1. Quantitation of the K+ signal was achieved by reference to an external standard of KCl/dysprosium nitrate as well as by reference to the proton signal from tissue water. In vitro NMR studies of isolated tissue showed a K+ visibility (NMR K+/total tissue K+) of 96%, 62 +/- 8%, 47 +/- 1.9%, 45 +/- 3.5%, and 43 +/- 2.5% for blood, brain, mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 12 publications
(10 reference statements)
0
20
1
Order By: Relevance
“…In our initial studies (reported herein) of in vitro rat thigh muscle carried out in a spectrometer having a 7.0 T magnetic field strength, we observed higher detectability (57 t 5%) than had been previously reported ( 4 ) .…”
Section: Introductioncontrasting
confidence: 43%
See 2 more Smart Citations
“…In our initial studies (reported herein) of in vitro rat thigh muscle carried out in a spectrometer having a 7.0 T magnetic field strength, we observed higher detectability (57 t 5%) than had been previously reported ( 4 ) .…”
Section: Introductioncontrasting
confidence: 43%
“…Measurements of the 39K NMR signal in biological tissues (1)(2)(3)(4) have shown that not all the potassium present is detectable when compared to chemical analysis methods such as atomic emission or absorption spectroscopy. Many of these studies showed the relative amount of potassium detected, commonly termed NMR visibility, to be around 40%, although there was some variability between tissues (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a TmDOTP shift reagent was used to assist 39 K NMR measurement of intracellular potassium during ischemia in the perfused guinea pig heart [234]. A number of studies have demonstrated the usefulness of 39 K NMR for in vivo measurement of potassium levels and its transport in a range of different rat tissues including blood, brain, muscle, kidney, liver, testes and mandibular salivary gland [235][236][237][238]. A number of feasibility studies have also been performed for 39 K-MRI analysis of human muscle ( Figure 17) and brain [239][240][241].…”
Section: F Ementioning
confidence: 99%
“…Several efforts have been made to assess the detectability and the physical properties of these nuclei which are important for their quantification in different tissues by means of NMR [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%